Edukasi tentang Kanker Serviks pada Masa Pandemi Covid-19 di Kelurahan Beringin Wilayah Kerja Puskesmas Koni Kota Jambi - Ratu Kusuma (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Cervical cancer is caused by the human papilloma virus and various other risk factors. The incidence of cervical cancer in Indonesia is around 23.4/100,000 population with an average death rate of 13.9/100,000 population. Data from the Medical Record for the Family Planning Program, Kespro, IVA Test and PKPR at Puskesmas Koni Jambi City (until September 2021) reported that there were 1932 PUS and 2803 WUS spread over 4 urban villages. Based on the initial survey, two problems were found “the problem of PUS/WUS and the problem of the program”. The purpose of this education is to increase knowledge, change attitudes and change actions. The education was held at RT 16 of the Kelurahan Beringin on January 11, 2022 for 24 WUS from RT 15, 16 and 17 which was held in conjunction with the implementation of the Posyandu Balita. The activity begins with a pretest, then the implementation of education for ± 50 minutes through lectures, discussions and questions/answers, as well as using power point. After the delivery of the material, a posttest was conducted again with the same questions on the pretest. The results obtained are an increase in the average knowledge of WUS by 1.7; an increase in the average attitude of 2,3; and education about cervical cancer was able to change the behavior of participants where there were 3 WUS who came to the Puskesmas Koni to do an IVA-test after attending the education. Whereas previously none of the 24 WUS had never done the examination because of fear even though they had experienced vaginal discharge from several months to several years ago. This means that the implementation of this education has been proven to change WUS behavior for the better.